Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Photoelectrochemical properties of electrochemically deposited CdIn2S4 thin films - Kokate, A. V.; Asabe, M. R.; Delekar, S. D.; Gavali, L. V.; Mulla, Imtiaz S.; Hankare, P. P.; Chougule, B. K. (Journal of Physics and Chemistry of Solids, 2006)
Thin films of CdIn2S4 have been deposited on to stainless steel and fluorine-doped tin oxide (FTO)-coated glass substrates from aqueous acidic bath using an electrodeposition technique. Ethylene diamine tetra-acetic acid (EDTA) disodium salt is used as complexing agent to obtain good-quality deposits by controlling the rate of the reaction. The different preparative parameters like concentration of bath, deposition time, bath temperature, pH of the bath have been optimized by the photoelectrochemical (PEC) technique in order to get good-quality photosensitive material. Different techniques have been used to characterize CdIn2S4 thin films. Optical absorption shows the presence of direct transition with band gap energy 2.17 eV. The X-ray diffraction (XRD) analysis of the as-deposited and annealed films showed the presence of polycrystalline nature. Energy-dispersive analysis by X-ray (EDAX) study for the sample deposited at optimized preparative parameters shows that the In-to-Cd ratio is almost 2 and S-to-Cd ratio is almost 4. Scanning electron microscopy (SEM) for samples deposited at optimized preparative parameters reveals that spherical grains are uniformly distributed over the surface of the substrate indicates the well-defined growth of polycrystalline CdIn2S4 thin film. PEC characterization of the films is carried out by studying photoresponse, spectral response and photovoltaic output characteristics. The fill factor (ff) and power conversion efficiency (eta) of the cell are 69 and 2.94%, respectively. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Thin films; X-ray diffraction

Ferroelectric and ferromagnetic properties of (x)BaTiO3+(1-x)Ni0.94Co0.01Cu0.05Fe2O4 composite - Devan, R. S.; Deshpande, S. B.; Chougule, B. K. (Journal of Physics D-Applied Physics, 2007)
A group of elastically coupled ferroelectric and ferrite composites with the general formula (x) BaTiO3 + (1 - x) Ni0.94Co0.01Cu0.05Fe2O4 (where x = 0.85, 0.70 and 0.55) was prepared by the standard ceramic reaction method. The x-ray diffraction pattern of the composite reveals a spinel phase formation for the ferrite and perovskite phase formation for the ferroelectric phase without any other phase. The SEM micrographs were taken to determine the average grain size. The sintered composites exhibit typical hysteresis loops at room temperature. The effect of constituent phase variation on the hysteresis behaviour and the dielectric properties was examined. The parameters such as spontaneous polarization (P-s), breakdown voltage (E-b) and saturation magnetization (M-s) of the composites vary with the ferroelectric/ ferrite content. The temperature dependence of dielectric behaviour at a frequency of 1 kHz was also studied. With increasing content of BaTiO3, the dielectric constant increases and the Curie temperature decreases.

Magnetic and dielectric properties of nanophase manganese-substituted lithium ferrite - Hankare, P. P.; Patil, R. P.; Sankpal, U. B.; Jadhav, S. D.; Mulla, Imtiaz S.; Jadhav, K. M.; Chougule, B. K. (Journal of Magnetism and Magnetic Materials, 2009)
Nanocrystalline manganese-substituted lithium ferrites viz. Li0.5Fe2.5-xMnxO4 (2.5 <= x >= 0) were prepared by sol-gel autocombustion method. X-ray diffraction analysis confirmed that as the concentration of manganese increases the cubic phase changes to the tetragonal phase. The variation of saturation magnetization was studied as a function of manganese content. All the compositions indicate that they are ferrimagnetic in nature. The dielectric constant, dielectric loss tangent and ac conductivity of all samples were measured at room temperature as a function of frequency. These parameters decrease with increase in frequency for all of the samples. The substitution of manganese plays an important role in changing the structural and magnetic properties of these ferrites. The compositional variation of dielectric constant and d.c. resistivity shows an inverse trend of variation with each other. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: dielectric constant; Ferrite; Magnetization; X-ray diffraction

Synthesis, characterization and effect of sintering temperature on magnetic properties of MgNi ferrite prepared by co-precipitation method - Hankare, P. P.; Jadhav, S. D.; Sankpal, U. B.; Chavan, Santosh S.; Waghmare, K. J.; Chougule, B. K. (Journal of Alloys and Compounds, 2009)
Mixed MgNi ferrites with composition Mg(0.5)Ni(0.5)Fe(2)O(4) where the mole fraction for Ni (x = 0, 0.25, 0.75, 0.5 and 1) were prepared by following co-precipitation method at temperature 110 degrees C and maintaining a pH of solution equal to 9.5 enable to achieve large particle surface area. The resultant materials obtained in powder form were sintered at different temperatures. Thermogravimetry (TGA), X-ray diffraction (XRD) and scanning electron microscopy, technique were applied to obtain structural parameters. The XRD patterns reveal the presence of(311) peak as the most intense one. The intensity of XRD peak increases with increase in sintering temperature. The saturation magnetization values showed increasing trend with increase in sintering temperature from 2.37 to 29.76 emu/g. These results along with the analysis of SEM micrographs are interpreted in terms of increase in particle grain size with increase in sintering temperature. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Ferrites; FT-IR; scanning electron microscopy; X-ray diffraction